Adaptation potential of medical students in distance learning - O. V. Toussova; O. V. Pavlova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2022)
Introduction. The coronavirus pandemic provoked a sharp transition from the classical form of education to distance learning, which has become widespread over the past year and a half. Both students and professors are forced to adapt to the changing conditions of learning and life in general. The current situation of uncertainty caused stress reactions and actualized the adaptive potential of the psyche. There are practically no studies on this topic, which explains the novelty and relevance of this work.Methods and materials. The article is devoted to the study of adaptive features of medical students in distance learning. To study adaptive features, a multilevel personality questionnaire (MLPQ) «Adaptability» was used (A. G. Maklakov, S. V. Chermyanin, 1993). To study the causes of educational stress in students and strategies for coping with stress, the Lazarus coping test and the test for educational stress (Yu. V. Shcherbatykh) were used. To study the attitude of students to full-time and distance learning, a specially designed questionnaire was used. Statistical processing was carried out using SPSS Statistics 21.Results. The study was conducted in the spring of 2021. 100 first-year students of Pavlov University participated in it. The average age of the sample was (18.32±1.5); among them: 29 men and 71 women. The leading causes of educational stress were: a large study load (7.32), a large amount of educational material to memorize (7.20), difficulty in understanding the material (6.99) and the presence of working off (6.82), which were introduced to eliminate debt. The leading coping strategies in distance learning were «self-control» (13.29), «problem solving planning» (13.21) and «positive reassessment» (12.99). The most common ways to cope with stress were sleep (17 %), delicious food (15 %), socializing with friends (14 %), outdoor activities (13 %), and support or advice from parents (12 %). Distance learning students had an average level of adaptive potential. Students with a higher adaptive potential in dealing with stress significantly more often (p≤0.01) use the strategies of problem solving planning and positive reassessment, while students with a lower adaptive potential significantly more often (p≤0.05) in a stress situation use «accepting responsibility» and «escape-avoidance» copings.Conclusions. The conducted study allowed to identify the causes of students’ educational stress, strategies of behavior and coping with stressful situations, which should be taken into account in the organization of the learning process and in the work of a psychological service to increase the acquisition of knowledge and academic success of students. The obtained results made it possible to identify the advantages and disadvantages of full-time and distance learning, which allows us to make an assumption about the optimal combination of both forms in the further educational process.